Tiller population density and tillering dynamics in marandu palisade grass subjected to strategies of rotational stocking management and nitrogen fertilization - doi: 10.4025/actascianimsci.v34i3.13739 - Fialho, Cleunice Auxiliadora; Silva, Sila Carneiro da; Gimenes, Flávia Maria de Andrade; Gomes, Marcelo Barcellos; Berndt, Alexandre; Gerdes, Luciana (Acta Scientiarum. Animal Sciences, 2012)
The objective of this experiment was to evaluate tiller population density and the dynamics of the tillering process in marandu palisade grass subjected to strategies of rotational stocking management and nitrogen fertilization. Treatments corresponded to combinations between two targets of pre-grazing conditions (sward surface height of 25 and 35 cm) and two rates of nitrogen application (50 and 200 kg ha-1 year-1), and were allocated to experimental units according to a 2 x 2 factorial arrangement in a randomised complete block design, with four replications. The following response variables were studied: initial (TPDi), intermediate (TPDm) and final (TPDf) tiller population density as well as the rates of tiller appearance (TAR) and death (TDR) and the tiller population stability index (SI). TPDi was similar to all treatments, with differences in tiller population density becoming more pronounced as the experiment progressed, resulting in larger TPDf on swards managed at 25 cm pre-grazing height. Tiller death was larger on swards managed at 35 cm, with differences in tiller appearance being recorded only from February 2010 onwards. Stability of tiller population was higher on swards managed at 25 cm pre-grazing height. Overall, there was no effect of nitrogen on the studied variables, and the most adequate grazing strategy corresponded to the pre-grazing height of 25 cm, regardless of the nitrogen application rate used.